JLU-H: A novel lunar highland regolith simulant for use in large-scale engineering experiments. (15th October 2022) - Sun, Xumin; Zhang, Rui; Li, Xiujuan; Zou, Meng; Wang, Chu; Chen, Lei
Abstract: High-fidelity lunar soil simulants are expensive and limited in quantity, which is difficult to meet the needs of large-scale engineering investigations about drilling, excavation or drop tests of spacecraft. For large-scale engineering experiments, the mechanical properties of simulants are more important because they will affect the accuracy and credibility of results. To satisfy the needs of large-scale engineering experiments, this study presents a new lunar highland soil simulant (JLU-H) which was made entirely of naturally available anorthosite complex without any added materials or minerals. The geotechnical properties of JLU-H, such as chemical composition, particle morphology, particle size distribution, specific gravity, bulk density, maximum and minimum density, and shear strength, were determined through a series of indoor tests, and the results were compared with data from Apollo 16 lunar soil sample parameters and other extant highland simulants. The results show that JLU-H can be used as a mechanical substitute for lunar highland soil, and its mechanical property parameters have good similarity with other highland simulants. Although the simulant is not fully representative of the Apollo 16 regolith samples in terms of chemical composition, it is generally close in terms of mineralogical composition. Moreover, compared with other highland simulants, JLU-H has the advantages of low price and the possibility of mass production.